Translation of the Qur'an Bebaso Plembang (Study of its Cultural Function and Preservation) - Trawina Trawina; Halimatussa'diyah, Halimatussa'diyah; Sulaiman M. Nur (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
This article aims to find out the cultural functions and maintenance of the Baso Plembang Qur'an translation. By using qualitative methods and Edi Sedyawati's cultural theory approach in his work Indonesian in Culture, namely protection, development and utilization, the results and conclusions show that: first, the function of the presence of the Baso Plembang Qur'an translation is one of which can facilitate the local community to understand the contents of the Qur'an, so that it can be used as a guide to life and provide religious services for Muslims in Palembang city. Secondly, the translation of the Baso Plembang Qur'an is a physical form of culture that is evidence of the consistency of the process of maintaining cultural heritage, namely the culture owned by every region in Indonesia, even the world. Based on the theory of cultural preservation (sustainanble tourism) for the maintenance of the Baso Plembang al-Qur'an translation, the protection of the Baso Plembang al-Qur'an translation is not a form of preserving the Qur'an, but rather an effort to translate it as a form of realization of the protection of the Palembang city language culture. Its development is carried out by printing it and disseminating it free of charge to various communities. Meanwhile, utilization is a form of community concern by holding courses or publishing books that talk about Baso Plembang and the translation of the Qur'an Baso Plembang, supported by the role of UIN Raden Fatah Palembang which carries Malay civilization as its distinction.